An investigation into outsider sculpture with special reference to D.C. van der Mescht - Cowley, Kerstin (Rhodes University, Faculty of Humanities, Department of Fine Art, 1991)
It was both by luck and by accident that Dirk Charley van der Mescht's creations were discovered as a topic for research ... a recluse who lived out in what seemed to be the middle of nowhere. It was said of this man that he was a strange person who produced even stranger works. On investigation it was discovered that he was an Outsider sculptor by the name of D. C. van der Mescht. He and his family live at a small railway siding, known as Zuney, eighteen kilometres west of Alexandria. Isolated, uneducated and untutored, he had created an environment of sculptures for no apparent reason at all. The only explanation he appeared to be able to offer is that: he just does it. Intro. p. 1.
Keywords: Outsider art; Art -- South Africa; Sculptors -- South Africa